Circular Economy for Nepal’s Sustainable Development Ambitions - Gavin Melles; Suresh Gautam; Richan Shrestha (Challenges)
The circular economy (CE) is a global proposition about decoupling consumption and production from resource use through reduce, reuse, and recycle (3R) and other r-strategies. In addition to promoting responsible consumption and production (SDG12), advocates claim the CE has wide-ranging impacts on sustainable development. Critics, however, see ambiguous definitions, practical conflicts with sustainability, and limited global appetite for a sustainability transition through the CE. Despite these criticisms, following the lead of other countries in Asia, Nepal has recently adopted the CE as an answer to waste recycling, sustainable tourism, energy generation, e.g., biogas, and and sustainable development in general. Until recently, the discussion about promoting circular r-strategies in Nepal, such as recycling, has lacked any critical review of circular claims for Nepal. Addressing this lack, this perspectives paper critically examines the scope and claims for the CE in Nepal relative to its sustainable development commitments. In contrast to the prevailing enthusiasm, our review finds that the CE may contribute little to Nepal’s development ambitions, that the EU influence is questionable, and the mainstream CE ignores a tradition of resource efficiency in Nepal. Our review suggests that other institutional demands must be met before with a transition to a sustainable circular economy can happen. The authors hope this perspectives paper will be read by governments, businesses, and other actors to inform a critical review of Nepal’s CE ambitions.